Hot-extrusion behavior of biodegradable Zn-Mg alloys. (2022) - Vidhish Naik, M.; Narasaiah, N.; Chakravarthy, P.; Arockia Kumar, R.
Abstract: Magnesium, zinc and iron-based alloys are the potential candidates for biodegradable implant applications and the effect of secondary processing on the biodegradability of these materials is of interest and being studied extensively. The evolution of gaseous hydrogen in magnesium-based alloys and higher corrosion rate limits the usage of these alloys, whereas, on the other hand, iron alloy's corrosion rate is too slow and leaves bulky corrosion products. The corrosion rate of Zn is in between the Mg and Fe, make it a potential alternate material. In the present study, pure Zn and Zn-Mg alloys are cast to different weight proportions and subjected to hot extrusion at different temperatures viz: 100, 150, 200, 250 and 300 °C. No surface defects were observed during extrusion of Zn at all temperatures, whereas Zn-Mg alloys were found to exhibit surface cracks at all temperatures except 200 and 250 °C. The presence of longitudinal tensile stresses at the surface due to frictional forces and inappropriate temperatures resulted in the development of cracks. The extruded samples were found to have fine microstructure as observed through an optical microscope. The XRD studies revealed the presence of the Mg2 Zn11 phase. The hardness of Zn was observed to increase by 26% after hot-extrusion which was due to the extensive grain refinement during extrusion.